Entre a Arte e a Psicanálise: a melancolia em Edvard Munch. - Mariana Rodrigues Festucci Ferreira (Affectio Societatis, 2015)
This text proposes a dialogue between the fields of Art and Psychoanalysis and their relationship with the pathos from the “pain of existence” in Edvard Munch. It is known that the “pain of existence” is present in all psychic structures, but it is sung at full power by the melancholic individual. In Edvard Munch, “the pain of existence”, more than being outlined in his work, is the fermenting component of his own life, his leitmotiv, as demonstrated in this paper that represents a summary of a research developed in the context of the specialization “Psychoanalysis and Language” at the Pontifical Catholic University of São Paulo (PUC-SP).